Uses of Precious Stones Among Arab Women Before Islam - حسنين عبد الرزاق حسن (College of Education for Women, 2019)
Precious stones enjoyed a high level of goodwill among people in the ancient world as they were considered as important source of their jewels, an effective medicine to cure their diseases and spiritual healing that bring optimism and happiness by holding it especially to those who believe their effects on the Human. Arab woman didn't abandon the interests of the neighbor civilizations as she coped with them and took what she desired of jewelry like pearls, sapphires and emerald. She used some of precious stones like antimony, magnet and bezoar in prescriptions for curing diseases and injuries. She also used turquoise, onyx and cat eye stone to prevent envy and Exorcism purposes as she thought that these stones could protect her from dangers and this was one of the common beliefs in the Arab civilization before Islam due to the large belief on myths and magic which was established by the magicians, priests and precious stones traders in order to control women's minds on behalf of their economic and social interests.